Simulation and human-computer interaction to analyze gene regulatory networks - Linn, Htet Oo (2014)
With rapid development in information technology, it has also become a great help to biological research and studies. Among the plentiful software applications developed to analyze Gene Regulatory Networks (GRN), GeneNetWeaver (GNW) is one of the most useful applications with its rich features and interactive Graphical User Interface (GUI). In order to make it the best out of the best ones, in this project, functionality of GNW has been enhanced by integrating more features into it. With these, the efficiency and effectiveness of the application will be fully utilized. In this project, we have integrated important features such as visualizing the gene expression datasets generated from GRN, which would greatly improve users’ convenience. Another essential feature we have developed is allowing users to modify the structure of GRN by deleting nodes (genes) or edges (interactions), which could simulate ‘knock-out’ experiments. Moreover, to help users realize the effects of particular modification to GRN structure, we have implemented the feature to compare the gene expression data before and after the modification. These new features will offer users great help to gain further understanding into the function of GRN.